Broadband Seismic Deployments for Imaging the Upper Mantle Structure in the Lützow-Holm Bay Region, East Antarctica. (29th August 2011) - Kanao, Masaki; Usui, Yusuke; Inoue, Tomofumi; Yamada, Akira
Abstract : Broadband seismic deployments have been carried out in the Lützow-Holm Bay region (LHB), Dronning Maud Land, East Antarctica. The recorded teleseismic and local events are of sufficient quality to image the structure and dynamics of the crust and mantle of the terrain. Passive seismic studies by receiver functions and shear wave splitting suggest a heterogeneous upper mantle. Depth variations in topography for upper mantle discontinuities were derived from long period receiver function, indicating a shallow depth discontinuity at 660 km beneath the continental area of LHB. These results provide evidence of paleo upwelling of the mantle plume associated with Gondwana break-up. SKS splitting analysis anticipated a relationship between "fossil" anisotropy in lithospheric mantle and past tectonics. Moreover, active source surveys (DSSs) imaged lithospheric mantle reflections involving regional tectonic stress during Pan-African and succeeding extension regime at the break-up. By combining the active and passive source studies of the mantle structure, we propose an evolution model of LHB for constructing the present mantle structure.